Pengaruh Penyuluhan Media Video Animasi Terhadap Pengetahuan Cara Memelihara Kesehatan Gigi Pada Siswa-Siswi Kelas III B SDN 41 Sungai Ambawang - Ningsih, Neny Setiawaty; Halimah, Halimah; Femala, Dian; Herlina, Rita; Susatyo, Jojok Heru (LPPM Institut Pendidikan Nusantara Global, 2024)
School age is the age when children need to get special attention so they know about how to maintain healthy teeth from an early age. Efforts to increase dental health knowledge can be done by conducting counseling using media that can attract the attention of school-age children. This study aims to determine the effect of counseling on animated video media on knowledge of how to maintain dental health. The research method used in this study was pseudo-experimental research with a sample of 30 respondents and sampling using total sampling techniques. Data collection was carried out using pretest and posttest questionnaire sheets and animated video media. The results of this study note that knowledge before counseling using video animation media is in the good category by 10% while after counseling using video animation media is in the good category by 90%. Based on the results of the discussion obtained, it can be concluded that the use of video animation media aids in conducting counseling can increase children's knowledge about how to maintain dental health.